2019
DOI: 10.1155/2019/5837832
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Macular Hole: Diagnosis, Natural History, and Management

Abstract: Traumatic macular hole occurs most often in young men and can present after various types of injuries. Traumatic macular holes result from anteroposterior and tangential vitreoretinal traction and may exhibit concurrent additional pathologies such as Berlin’s edema and subretinal fluid. Optical coherence tomography can play an essential role in patient management both at presentation and during follow-up. Initial management consists of observation, but macular hole repair can be performed if spontaneous resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 39 publications
0
25
0
5
Order By: Relevance
“…Several macular pathologies have been reported that may develop secondary MH such as cystoid macular edema, subretinal fluid due to rhegmatogenous retinal detachment, and SMH [2][3][4][5][6][7][8][9][10]. In most of the secondary MH associated with SMH, the SMH was caused by rupture of a retinal arterial macroaneurysm (RAM) [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several macular pathologies have been reported that may develop secondary MH such as cystoid macular edema, subretinal fluid due to rhegmatogenous retinal detachment, and SMH [2][3][4][5][6][7][8][9][10]. In most of the secondary MH associated with SMH, the SMH was caused by rupture of a retinal arterial macroaneurysm (RAM) [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Formation of an idiopathic MH has been attributed to mechanical forces exerting tangential traction at the vitreomacular interface. Secondary MH may develop in association with trauma [2], macular edema [3], retinal detachment [4], choroidal neovascularization [5][6][7], or submacular hemorrhage (SMH) [8][9][10]. Spontaneous closure is a rare event [7,[10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported uncertain mechanism of TMH [ 3 , 7 , 9 ] with many hypotheses and speculations been put forward. The early-onset TMH is thought to be as a result of anteroposterior compression caused by blunt trauma, followed by a rebound contrecoup resulting in vitreofoveal traction [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of TMH is 1.4% in closed-globe trauma and 0.15% in open-globe injuries [ 2 ]. Due to its rarity, studies on TMH are limited [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…[7,12] Other potential causes of TMHs include laser injury, surgical trauma, lightning strikes, and electrical shock. [13] TMHs can result in severe central visual field loss. [7,13] Other ocular pathologies may develop concurrently with TMH, such as commotio retinae, hyphema, vitreous or subretinal hemorrhage, retinal detachment, uveal tears, and choroidal rupture.…”
Section: Traumatic Mhs (Tmhs)mentioning
confidence: 99%